Expression and signaling of NGF in the healthy and injured retina. (April 2017) - Garcia, Tarcyane Barata; Hollborn, Margrit; Bringmann, Andreas
Graphical abstract: Highlights: In the neural retina of adult animals, proNGF and mature NGF are mainly expressed by RGCs and glial cells such as Müller cells and microglia. Expression of both proNGF and p75NTR is elevated in various animal models of retinal degeneration. Alterations in the balance of both proNGF/mature NGF and TrkA/p75NTR expression may be implicated in retinal cell death. Administration of exogenous NGF has shown some success to ameliorate retinal degeneration. Cell-based therapy may represent a promising method to increase the availability of retinal NGF with long-term neuroprotective effect. Abstract: This review summarizes the present knowledge concerning the retinal localization of the nerve growth factor (NGF), its precursor proNGF, and the receptors TrkA and p75 NTR in the developing and mature rodent retina. We further discuss the changes in the expression of NGF and the receptors in experimental models of retinal disorders and diseases like inherited retinitis pigmentosa, retinal detachment, glaucoma, and diabetic retinopathy. Since proNGF is now recognized as a bioactive signaling molecule which induces cell death through p75 NTR activation, the role of proNGF in the induction of retinal cell loss under neurodegenerative conditions is also highlighted. In addition, we present the evidences for a potential therapeutic intervention with NGF for the treatment of retinal neurodegenerative diseases. Different strategies have been developed and experimentally tested in mice and rats in order to reduce cell loss and Müller cell gliosis, e.g., increasing the availability of endogenous NGF, administration of exogenous NGF, activation of TrkA, and inhibition of p75 NTR . Here, we discuss the several lines of evidence supporting a protective effect of NGF on retinal cell loss, with specific emphasis on photoreceptor and retinal ganglion cell degeneration. A better understanding of the mechanisms underlying the effects of NGF and proNGF in the modulation of neurodegeneration and gliosis in the retina will help to develop efficient therapeutic strategies for various retinal diseases.